Sustainability and Prolonging Rechargeable Battery Life: A Sensor Device Review - Sahu, Swati; Tiwari, Sanjay (Journal of Electronics and Electrical Engineering, 2023)
Rechargeable batteries have recently experienced increases in productivity and the economy, solidifying their dominance in energy-intensive cultures. Regular performance monitoring is required to lessen the adverse environmental effects of batteries in the face of increased demand. The distinctive features of Lithium-Ion Batteries (LIBs) make them an ideal choice for energy storage. Battery Management Systems (BMSs) are needed to make sure that LIB systems are safe and operate effectively. Critical problems in the existing structure and operation of BMSs are their limited data storage capacity and weak computational power. This paper studies the idea and architecture of cloud-based smart BMSs and offers some viewpoints on their performance, usability, and advantages for upcoming battery applications. While some of the benefits of sensors have been recognized for more than a hundred years, the combination of diverse sensing technologies with novel battery platforms has the potential to revolutionize the sector by changing how both new and old lithium-ion devices are used. This paper also highlights current advances and their associated benefits focusing on electrochemical, mechanical, acoustic, and optical sensors that can potentially boost battery sustainability and longevity.